Mathematical Analysis of Hemodynamic Parameters of Blood Flow in an Artery - Kafle, Jeevan; Panta, Kamal; Gautam, Pushpa Nidhi; Pokharel, Chudamani (Mathematics Education Forum Chitwan, 2022)
In blood rheology we study volume flow rate, blood pressure, velocity, viscosity and shear stress of blood. Cross-sectional area plays an important role for smooth flow of the blood. But some other parameter like composition of blood, length of vessel also affects in the flow rate and pressure of blood. Velocity and volume flow rate are derived by using Poiseuille’s equation.This work presents a mathematical model of blood flow that was created using the N-S equations and computer simulation. Graphs are used to analyze the results.